Online Teaching and Learning Experiences During the COVID-19 Pandemic - A Comparison of Teacher and Student Perceptions - Lei, Sut Ieng; So, Amy Siu Ian (Journal of hospitality & tourism education, 2021)
Understanding teachers' and students' perceptions of online teaching and learning has been an important and popular research topic. As the COVID-19 outbreak has made online learning the best available option under social distancing and quarantine policies, the conversation on the effectiveness of online learning and its potential to strive in the future continues. However, as this conversation has received relatively less attention in the tourism and hospitality literature, this study investigated the online teaching and learning experiences of university teachers and students respectively the tourism and hospitality programs. Using an online survey distributed in March 2020, data were collected from 117 academic staff members and 491 students from over 15 higher education institutions that offer tourism and hospitality subjects in China. The two data sets (teachers and students) were compared using independent samples t-test and multi-group structural equation modeling. The findings reveal the similarities and differences between the two groups in terms of the factors affecting online teaching and learning satisfaction. Managerial implications are suggested to institutions and educators to enhance teachers' online teaching satisfaction and students' online learning satisfaction.